The Long Slump - Hall, Robert E (American Economic Review, 2011)
In a market-clearing economy, declines in demand from one sector do not cause large declines in aggregate output because other sectors expand. The key price mediating the response is the interest rate. A decline in the rate stimulates all categories of spending. But in a low-inflation economy, the room for a decline in the rate is small, because of the notorious lower limit of zero on the nominal interest rate. In the Great Depression, substantial deflation caused the real interest rate to reach high levels. In the Great Slump that began at the end of 2007, low inflation resulted in an only slightly negative real rate when full employment called for a much lower real rate because of declines in demand. Fortunately, the inflation rate hardly responded to conditions in product and labor markets, else deflation might have occurred, with an even higher real interest rate. I concentrate on three closely related sources of declines in demand: the buildup of excess stocks of housing and consumer durables, the corresponding expansion of consumer debt that financed the buildup, and financial frictions that resulted from the decline in real-estate prices. (JEL E23, E24, E31, E32, E65)